Taxa de gestação em éguas inseminadas com sêmen resfriado de jumentos, utilizando diluidor à base de leite UHT desnatado: gema de ovo com duas concentrações de glicose - Nicole Melo de Araujo Rocha (2012)
The present study was conducted at Bálsamo farm, located in Luz, Minas Gerais, Brazil, from October 2011 to May 2012. The aims of this study were to evaluate a) the effect of two extenders containing UHT skim milk, egg yolk and glucose (D1 and D2) on sperm preservation and fertility of mares inseminated with jackass cooled semen at 5ºC; b) the behavior of spermatozoa from different jackasses after cooling, based on in vitro parameters and on fertility of inseminated mares; c) the effects of the age of the mares, reproductive status, interval between artificial insemination and ovulation and number of artificial inseminations per cycle on mare fertility. Therefore, 171 cycles of 122 mares of undefined breed, randomly distributed in two groups (TI and TII) were used. As semen donors, three jackasses of the Pêga breed were used. After collection, the semen was diluted in two different extenders and used for artificial insemination within 14.56±0.06 hours of collection or 14.13±0.06 hours after cooling. The inseminations occurred on mondays, wednesdays and fridays, after the detection of a follicle with 3.0 cm diameter in one of the ovaries, until ovulation. The pregnancy was detected by ultrasonography starting at 11º day after ovulation. The conception rates per cycle were 67.90% for D1 and 55.56% for D2 and it did not differ (p>0.05) between the jackasses. The in vitro seminal parameters were different (p<0.05) between the jackasses, but it did not affect (p>0.05) the mare fertility. Semen motility remained above 70% and vigor was greater than 3 for all of the storage period in both extenders. Age, reproductive status, interval from insemination to ovulation and number of inseminations per cycle did not affect (p>0.05) mares fertility after insemination with diluted and cooled jackass semen. Considering the current experimental conditions, the protocols tested may be recommended to commercial stud operations.